TNF microsatellites polymorphism is associated with rheumatoid arthritis. Confirming evidence in northwestern Colombians (2007)
Objective: To examine the contribution of tumor necrosis factor alpha (TNF) microsatellite (a to e) polymorphism to the genetic risk of developing rheumatoid arthritis (RA) in a northwestern Colombian population. Methods: This was an association study in which 108 RA patients and 222 matched individuals were enrolled. HLA-DRB1 and DQB1 polymorphisms were evaluated to examine for linkage disequilibrium between these loci and TNF microsatellites. Genotyping was performed using denaturing polyacrylamide gels and polymerase chain reaction-sequence techniques. Results: By unconditional logistic regression analysis, the TNFa6 allele (OR= 2.37, 95%CI 1.07-5.24) and the TNFb4 allele (OR= 3.01, 95%CI 1.07-9.00) were observed to be associated with disease. These associations were independent of HLA-DR and HLA-DQ since linkage disequilibrium between HLA class II and TNF microsatellites was not observed. In addition, patients with the TNFa8 allele had a five times greater risk of developing extra-articular manifestations as compared to patients without this allele (OR = 5.07, 95%CI 1.14-22.52), regardless of age and the duration of disease. Haplotype analysis disclosed a protective effect for TNFa7/b7/c1/d4/e3/-308G/-238G. Conclusion: These results confirm that the TNF locus exerts a primary influence on both susceptibility to and the severity of RA. © Copyright Clinical and Experimental Rheumatology 2007.